2015
DOI: 10.1007/s10750-015-2312-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeding choice and predation pressure of two invasive gammarids, Gammarus tigrinus and Dikerogammarus villosus, under increasing temperature

Abstract: International audienceIn most European freshwater ecosystems, the invasive gammarids Gammarus tigrinus and Dikerogammarus villosus strongly impair recipient communities through predation of a wide range of native invertebrates. Due to the effects of temperature on both the physiology and the behaviour of such ectotherms, understanding how global warming may influence their ecological impact is a research priority. These species were therefore exposed to three different food types to determine their detritivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
(59 reference statements)
3
32
0
Order By: Relevance
“…Most studies have reported a lower resistance of female gammarids to different stress (pollutants, hypoxia, salinity, temperature: McCahon & Pascoe, ; Hoback & Barnhart, ; Sornom et al ., ), potentially explaining the lower food consumption of females compared to males, relative to their size, as observed in our study. Several other investigators have reported sex‐related differences in food consumption by amphipods, but, contrary to our study, in most cases, food consumption was lower in males (Foucreau et al ., , ; Pellan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies have reported a lower resistance of female gammarids to different stress (pollutants, hypoxia, salinity, temperature: McCahon & Pascoe, ; Hoback & Barnhart, ; Sornom et al ., ), potentially explaining the lower food consumption of females compared to males, relative to their size, as observed in our study. Several other investigators have reported sex‐related differences in food consumption by amphipods, but, contrary to our study, in most cases, food consumption was lower in males (Foucreau et al ., , ; Pellan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schmidlin et al . () observed a slightly reduced feeding activity of G. fossarum above 16 °C, while that of males Dikerogammarus villosus decreased between 20 and 25 °C (Pellan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Boudouresque et al (2015) presents a bibliographic review of the functioning of Posidonia meadows (Posidonia oceanica seagrass meadow), summarizing the services associated with the Mediterranean ecosystem, specifically its necromass, which is particularly vulnerable and plays an important role in stabilizing coastal erosion and fixing carbon. Pellan et al (2015) show the impact of global warming on the ecological success of the invasive species Dikerogammarus villosus. Rocarpin et al (2015) demonstrate the key role played by functional niche plants in temporary Mediterranean marshes, it could be useful in developing water management plans, or even planning for how to adapt to a changing environment.…”
mentioning
confidence: 99%